Camphor Sulfonic Acid (CSA) doped Polyaniline as Conductive Polymer - ACHMAD NOUFAL (NIM : 10510058) ; Pembimbing Dr. Veinardi Suendo
Acid doping is a primary method to increase the conductivity of conductive polymer in the case of polyaniline (PANI). Recently, camphor sulfonic acid (CSA) has attracted much interest for researchers. This is due to the presence of sulfonic groups (-SO3-) in CSA structure which facilitate the doped PANI to interact with polar solvent so it will be easy to processed for various applications by means increase its solubility. In this research, various doping method have been carried out, such as doping with small mass percent ratio of CSA, mixing method, reflux method, and grinding method. Results from all of methods show that the grinding method produced the highest conductivity value which enhanced the conductivity of PANI-EB by 7 orders of magnitude. FTIR spectra of PANI-CSA show peaks 1028 and 1719 cm-1 that indicate the presence of sulfonic and carbonyl groups from CSA, respectively. The peak at 1225 cm-1 is characteristic band of protonation form of the conductive PANI. This was confirmed by the Raman spectra of PANI - CSA that shows a peak at 1346 cm-1 corresponses to the stretching vibration C (aryl) - N+ bond, while the peak at 1171 cm-1 corresponses to stretching vibration C-H bond (aromatic). UV -Visible spectra show that PANI - CSA provides several absorption bands that corresponse benzenoid ring (363 nm), quinonoid ring (886 nm), and polaronic structure (460 nm). Frequency response of the conductivity (σ(ω)) shows the semiconductor characteristic of PANI - CSA where the conductivity increases with frequency. Here, maximum conductivity attained by PANI-CSA at 30 Hz is 2,92 ÃƒÂ— 10-2 S cm-1 obtain grinding method with 2,5 mmol.